1982
DOI: 10.1111/j.1471-0528.1982.tb15067.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on uterine tract infections and the IUCD with special reference to actinomycetes

Abstract: Since the advent of the plastic IUCD, an increasing number of patients with clinical pelvic actinomycosis have been reported in the literature and in a very much larger number of women, actinomycetes have been identified in cervical smears, either by Papanicolaou stain or specific immunofluorescence. After a 3-year study, we have concluded that actinomycetes can readily be cultured wherl the growth of more rapidly growing anaerobes is inhibited by metronidazole and anaerobic culture is continued for up to 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In view of the essential role played by the removal of the IUD from the uterine cavity in the disappearance of genital colonization by Actinomyces, in our opinion, and as reported by authors such as Duguid et al [14], Arroyo and Quinn [18], Leslie and Garland [13], Antolín et al [16], Tendolkar et al [17], Ló pez-Olmos et al [12], Fiorino [10], Chardonnens et al [11], Rodriguez Costa et al [15], Schlaen et al [4], Fresnadillo et al [2], IUD removal, by itself, could be sufficient as an effective treatment for this process, eliminating the need to associate antibiotics.…”
Section: Discussionmentioning
confidence: 47%
“…In view of the essential role played by the removal of the IUD from the uterine cavity in the disappearance of genital colonization by Actinomyces, in our opinion, and as reported by authors such as Duguid et al [14], Arroyo and Quinn [18], Leslie and Garland [13], Antolín et al [16], Tendolkar et al [17], Ló pez-Olmos et al [12], Fiorino [10], Chardonnens et al [11], Rodriguez Costa et al [15], Schlaen et al [4], Fresnadillo et al [2], IUD removal, by itself, could be sufficient as an effective treatment for this process, eliminating the need to associate antibiotics.…”
Section: Discussionmentioning
confidence: 47%
“…Fiorino evaluated 92 patients having pelvic actinomycoses and concluded that on an average these patients had IUCD in situ for approximately 8 years 8 . There are studies that suggest that a plastic IUCD device is more prone to actinomyces infections and that these infections can be eradicated if this device is removed or replaced by a copper device 9 …”
Section: Discussionmentioning
confidence: 99%
“…was re covered from 2 patients with perianal infec tions, and from lUCDs removed from 3 pa tients with pelvic inflammatory disease. Pel vic actinomycosis as a complication in IUCD usage is well documented [15,16].…”
Section: Discussionmentioning
confidence: 99%